DISSOLUTION MECHANISMS OF GOETHITE IN THE PRESENCE OF SIDEROPHORES AND ORGANIC ACIDS - Reichard P.U.; Kretzschmar R.; Kraemer S.M. (My University, 2007)
In dynamic natural systems such as soils and surface waters, transient biogeochemical processes can induce strong chemical non-steady-state conditions. In this paper, we investigate the effects of non-steady-state conditions on ligand-controlled iron oxide dissolution. The rates of goethite dissolution at pH 6 in the presence of low molecular weight organic acids (oxalate, citrate or malonate) were observed. Non-steady-state conditions were induced by rapid additions of fungal, bacterial or plant siderophores. In the presence of the low molecular weight organic acids, dissolved iron concentrations are below detection limit as predicted by equilibrium solubility calculations. The rapid addition of the siderophores triggered reproducible, fast dissolution of kinetically labile iron from the iron oxide surface. The same effect was observed upon rapid additions of high citrate concentrations to goethite-oxalate suspensions. The concentration of the labile iron pool at the mineral surface was a function of the surface concentration of the low molecular weight organic acids and of the reaction time before addition of the siderophores. Isotopic exchange with 59Fe independently confirmed the existence of the labile iron pool before addition of the siderophore. A dissolution mechanism was elucidated that is consistent with these observations and with accepted models of ligand-controlled dissolution. We conclude that the fast dissolution reaction observed here is an important process in biological iron acquisition and that it is based on a general geochemical mechanism. © 2007 Elsevier Ltd. All rights reserved.
Keywords: goethite